(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In the present conditions, where a democratic and legal society is being established in the Republic of Uzbekistan, the ability of the young generation to think independently and freely allows them to express their personal attitude to the events taking place. The formation of a personal point of view in relation to the changes taking place in the social existence is one of the important aspects showing the activity of the individual, moreover, a person with an independent opinion can freely demonstrate his capabilities and abilities. The main goal of successfully conducted educational reforms is to bring up a mature person with a free, independent opinion and a qualified specialist.